A Thermodynamic Study on the Binding of Polyethyleneglycol 1500 Stearic Acid with Lysozyme - Mohsen Mohammadian; G. Rezaei Behbehani; Bahram Ghalami-Choobar; A. Divsalar (Orbital: The Electronic Journal of Chemistry, 2019)
Thermodynamics of the interaction between copolymer of Stearic acid + polyethyleneglycol 1500 mixtures, S1500, with lysozyme was investigated at pH 7.0 and 27 °C in phosphate buffer by isothermal titration calorimetry, ITC. The extended solvation model was used to reproduce the enthalpies of S1500+lysozyme interactions. The solvation parameters recovered from the extended solvation model, attributed to the structural change of lysozyme. The binding parameters found for the interaction of S1500 with lysozyme, indicate that there are 2 set of binding sites in this interaction. The observations indicated that the low S1500 content induced protein stabilization, whereas at the high S1500 concentration, much more stabilization occurred in lysozyme structure.DOI: http://dx.doi.org/10.17807/orbital.v11i7.1373